Automation of the interpolation of pre-processor basic data for program complex “press 3D URAL” - Brigadnov, Igor Albertovich; Sidorov, Dmitry V.; Mozer, Sergey P. (Journal of Advanced Computer Science & Technology, 2013)
To automate the process of forming the baseline data pre-processing software package block PRESS 3D URAL [1], designed to solve engineering problems of Mining Geomechanics encouraged to use triangulation objects 2D space mining plans and their subsequent transformation into a 3D computational model.